Clinical Characteristics and Evolution of Giant Cell Tumor Occurring in Paget's Disease of Bone. (February 2015) - Rendina, Domenico; De Filippo, Gianpaolo; Ralston, Stuart H; Merlotti, Daniela; Gianfrancesco, Fernando; Esposito, Teresa; Muscariello, Riccardo; Nuti, Ranuccio; Strazzullo, Pasquale; Gennari, Luigi
ABSTRACT Patients with Paget's bone disease (PDB) have an increased risk of developing giant cell tumor (GCT). This study was performed to evaluate the clinical characteristics and evolution of GCT complicating PDB and to compare these clinical characteristics to those observed in two large PDB cohorts, the PDB Italian Registry and the United Kingdom's Multi‐Centre Randomised Controlled Trial of Symptomatic Versus Intensive Bisphosphonate Therapy for Paget's Disease (PRISM) study. A systematic literature review identified 117 cases of PDB complicated by GCT (PDB‐GCT), which involved the skeletal sites affected by PDB (110 patients) or the extraskeletal tissues adjacent to affected bones (7 patients). In contrast to what previously reported for GCT patients without GCT patients (83.2%) were white and one‐fourth of them (24.8%) had multifocal GCTs. Compared to PDB patients without GCT, PDB‐GCT patients showed a higher male/female ratio (2.1 versus 1.2) and more severe disease (age at PDB onset 52.1 ± 12.1 versus 63.3 ± 10.6 years; number of affected sites 6.1 ± 2.9 versus 2.34 ± 1.6; prevalence of polyostotic PDB 93.3% versus 60.6%). The mortality rate of PDB‐GCT patients was higher than those occurring in GCT patients without PDB (about 50% versus 0% to 5% at 5 years) or in PDB patients without GCT (log rank = 29.002). Moreover, up to 98% of PDB‐GCT cases had elevated total alkaline phosphatase levels at neoplasm diagnosis, suggestive of active PDB. Importantly, PDB‐GCT patients from Southern Italy (45.6% of all GCT patients) showed a higher prevalence of multifocal GCT (51.7%) and of positive familial history for PDB (70.8%) and GCT (65.0%). Finally, indirect evidence suggests a decline in the incidence of GCT in PDB patients. The occurrence of GCT in PDB patients is associated with severe disease and reduced life expectancy of affected patients. The increased prevalence of familial diseases in PDB‐GCT patients from Southern Italy suggests a founder effect. The observed changes over time in the incidence of GCT in PDB patients could be related to improved clinical management and/or living conditions of patients. © 2014 American Society for Bone and Mineral Research.